CONSTRUCTION OF RECOMBINANT PLASMID PBS0E-MISTIC-CYP71AV1-CPR - Gideon, Gian
Artemisia annua, a plant used as a commercial and economical source of artemisinin, has a low artemisinin content, which limits the commercialization of this product. One effort to overcome this is through the development of biosynthetic pathway engineering through genetic engineering of enzymes that play a role in the production of artemisinin using microbes. CYP71AV1 and CPR are two enzymes involved in the biosynthesis of artemisinic acid and pBS0E is a shuttle vector from Escherichia coli and Bacillus subtilis. By constructing the recombinant plasmid pBS0E-Misticcyp71av1-CPR, it is expected that the recombinant plasmid can be produced easily and quickly in E. coli, and can be used for the expression of cyp71av1 and CPR in B. subtilis. Currently, B. subtilis is attracting more attention to be developed into a terpenoid cell factory because of its generally regarded as safe (GRAS) status and high isoprene precursor biosynthesis capacity. In this experiment, the recombinant plasmid pBS0E-Mistic-cyp71av1-CPR was constructed. The cyp71av1 and CPR genes were from the cloning vector pUC57. Attempts to transfer these genes to the pBS0E expression vector require a subcloning process. The recombinant plasmid was transformed into E. coli. Construction and transformation of the recombinant plasmid pBS0E-Mistic-cyp71av1-CPR into E. coli have been carried out, but the colonies that grew were not confirmed to carry the transformed recombinant plasmid. Although it is suspected that the ligation results have successfully shown the integration of DNA fragments carrying the cyp71av1 and CPR genes into pBS0E, transformants that carried the recombinant plasmid have not been obtained.